Optimasi Kekuatan Tarik Belah Beton Mutu Tinggi Melalui Peningkatan Efektivitas Bakteri Pada Self-Healing Concrete - Andi Alepu; Teuku Budi Aulia; Yunita Idris (Jurnal Permukiman, 2024)
High-strength concrete has a higher compressive strength compared to regular concrete, making it an ideal choice for structures that bear heavy loads, such as tall buildings, bridges, and towers. However, the weakness of concrete lies in its susceptibility to tensile forces, leading to the development of microcracks that may potentially evolve into macrocracks without detection. To address this issue, an innovation known as Self-healing Concrete (SHC) has emerged, wherein bacteria such as solibacillus, bacillus, and staphylococcus are added to the concrete mix. These bacteria produce compounds that form calcium carbonate (CaCO3) deposits, autonomously closing microcracks through their metabolism. This research aims to enhance the lifespan of concrete and the safety of structures by incorporating bacteria into the concrete mix. Testing was conducted using cylinders with a diameter of 15 cm and a height of 30 cm, with initial cracks introduced after 7 days of immersion and compressive strength reaching 30 MPa, which is 80% of the planned compressive strength of 50 MPa. Testing was performed on day 28. The results of the split tensile strength tests using solibacillus bacteria showed an average of 4.46 MPa, bacillus bacteria with an average of 4.51 MPa, and staphylococcus bacteria with an average of 5.48 MPa. Scanning Electron Microscopy (SEM) results depicted substances related to calcite crystals in each bacterial concrete sample. The use of bacteria as a self-healing agent has a positive impact, including increased split tensile strength, reduced water absorption, and decreased concrete permeability.